Non-formal Astronomy Education in Brazil: Analysis of works published in national scientific events - Moraes, Leandro Donizete; Frango Silveira, Ismar (Technium Social Sciences Journal, 2020)
This article aims to reflect on research trends on non-formal education in astronomy through the analysis of national scientific events. In this state-of-the-art research, we use content analysis by Laurence Bardin and identify 328 papers presented in oral and panel communications. We analyzed this sample through five categories of analysis: Scientific Event; Year of publication; Region; Institution and Thematic Focus. Among the trends, research was presented in non-formal spaces, the use of technology and the approximation between formal and non-formal education through activities such as sky observations. As for the challenges, we identified few studies from the North, Northeast and Midwest. In addition, the history of indigenous, cultural and amateur astronomy, inclusion and astronomy is lacking research, showing that the area is still diffuse and needs closer ties between its various actors.